1974
DOI: 10.1111/j.1476-5381.1974.tb09732.x
|View full text |Cite
|
Sign up to set email alerts
|

CHOLINOMIMETIC EFFECTS OF AQUEOUS EXTRACTS FROM Carum copticum SEEDS

Abstract: An aqueous extract from roasted seeds of Carum copticum (omum) has cholinomimetic effects. It shows muscarinic effects on rabbit duodenum, guinea-pig ileum and rat jejunum, and on the blood pressure of rat and cat. These effects are blocked by atropine. It also has a nicotinic action on the frog rectus preparation and atropinized cat blood pressure. Its effect is potentiated by physostigmine and antagonized by cholinesterase or alkalinization. Paper and gas chromatography have confirmed the presence of acetylc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 3 publications
(3 reference statements)
1
14
0
Order By: Relevance
“…We found that aqueous extracts with roasted seeds had large amounts of acetylcholine and choline to explain its stimulant effect on isolated rat tissues. 10 Similar presence of acetylcholine and choline in aqueous extracts is reported in aqueous extracts from roasted spices. 14 Relaxation with cold omum extracts was also reported.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…We found that aqueous extracts with roasted seeds had large amounts of acetylcholine and choline to explain its stimulant effect on isolated rat tissues. 10 Similar presence of acetylcholine and choline in aqueous extracts is reported in aqueous extracts from roasted spices. 14 Relaxation with cold omum extracts was also reported.…”
Section: Discussionmentioning
confidence: 53%
“…14 Relaxation with cold omum extracts was also reported. 10 The present paper investigated the possible receptor mechanisms of these relaxant effects -anti-muscarinic, antihistaminic and adrenergic systems. Even uterine contractions induced by oxytocin were not relaxed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the Abana showed elevation of acetylcholine level by significant reduction of cholinesterase activity in brain of treated young and aged mice. Furthermore, ingredients Carum copticum, 35) Celastrus paniculatus, 19) Glycyrrhiza glabra, 16) Zingiber officianale, 27) Centella asiatica, 33) Withania somnifera, 36) have been reported to possess AChE inhibitory activity, which may facilitate the cholinergic pathways responsible for the improvement of memory exhibited by Abana.…”
Section: Discussionmentioning
confidence: 99%
“…Some biological effects of T. copticum such as anti-inflammatory (Thangam et al 2003), antifungal (Rasooli et al 2008), antiviral (Hussein et al 2000), anti-nociceptive (Hejazian et al 2008), anti-filarial (Mathew et al 2008), antioxidant activity (Bera et al 2004), analgesic (Kaur et al 2009), antimicrobial (Sharifi-Rada et al 2013) and also several therapeutic effects including anti-tussive (Devasankaraiah 1974), anti-vomiting (Gilani et al 2005), digestive stimulant (Boskabady et al 2003), hepatoprotective (Srivastava et al 1999) and lactogenic (Shaukat et al 2004) have been documented.…”
Section: Introductionmentioning
confidence: 99%